Are different markers of endometrial receptivity telling us different things about endometrial function?. (12th September 2020) - Hviid Saxtorph, Malene; Persson, Gry; Hallager, Trine; Birch Petersen, Kathrine; Eriksen, Jens O.; Larsen, Lise Grupe; Macklon, Nick; Hviid, Thomas Vauvert F.
Abstract: Problem: To what extent do endocrine, immunological, gene expression and histological markers of endometrial receptivity correlate? Method of study: Between November 2017 and September 2019, 121 women referred to a University Hospitals Fertility Clinic consented to inclusion in this cohort study. The women underwent timed endometrial biopsy followed by blood samples in a hormone‐substituted cycle. Of these, 37 women had just started IVF treatment, and the remaining 84 had experienced recurrent implantation failure following IVF/ICSI. The hormone‐substituted cycle consisted of initiation with oral oestradiol followed by addition of vaginal progesterone treatment for five full days. Endometrial biopsies were subject to histological examination, immune cell markers by immunohistochemistry (CD56 +, CD16 +, CD163 +, FoxP3) and gene expression microarray analyses with the endometrial receptivity array (ERA ® ) test (Igenomix). Plasma progesterone and oestradiol were measured on the day of biopsy. Results: CD56 + uterine natural killer (uNK) cell counts correlate with transcriptional markers of endometrial receptivity assessed by the ERA test. Endometrial maturation, receptivity and immunological markers were not correlated with mid‐luteal blood plasma progesterone level. Mid‐luteal serum oestradiol level correlated with markers of endometrial maturation and receptivity. The tests were carried out during a standard hormone substitution cycle, and the findings may not apply in the natural cycle. Conclusion: CD56 + uNK cell counts and endometrial receptivity assessed by the ERA test appear to be linked. Mid‐luteal progesterone levels were not correlated to the tested markers of endometrial receptivity. In contrast, mid‐luteal oestradiol level was inversely related to markers of endometrial receptivity and maturation.